2020
DOI: 10.1073/pnas.2005708117
|View full text |Cite
|
Sign up to set email alerts
|

Functional rewiring across spinal injuries via biomimetic nanofiber scaffolds

Abstract: The regrowth of severed axons is fundamental to reestablish motor control after spinal-cord injury (SCI). Ongoing efforts to promote axonal regeneration after SCI have involved multiple strategies that have been only partially successful. Our study introduces an artificial carbon-nanotube based scaffold that, once implanted in SCI rats, improves motor function recovery. Confocal microscopy analysis plus fiber tracking by magnetic resonance imaging and neurotracer labeling of long-distance corticospinal axons s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In addition, functional biomaterials can carry a variety of biomolecules such as growth factors, drugs, antibodies, genes, enzymes, and exosomes through physical, chemical, and biological modifications and help tissue repair through different therapeutic targets, and at the same time, by adjusting the electrical conductivity, mechanical properties, structural morphology, etc. of the material, the optimal therapeutic effect can be achieved [ 176 179 , 185 , 187 , 188 ].…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, functional biomaterials can carry a variety of biomolecules such as growth factors, drugs, antibodies, genes, enzymes, and exosomes through physical, chemical, and biological modifications and help tissue repair through different therapeutic targets, and at the same time, by adjusting the electrical conductivity, mechanical properties, structural morphology, etc. of the material, the optimal therapeutic effect can be achieved [ 176 179 , 185 , 187 , 188 ].…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…According to reports, collagen is used as the main component of the bioactive scaffold, through the preparation process and method to make it have a certain appearance characteristics and then modify it with the stromal cell-derived factors, neurotrophic factors (NT-3 and BFGF), genes, antibodies (cetuximab), and drugs (paclitaxel) which can effectively promote the migration and survival of endogenous neural stem cells and induce them to differentiate into neurons, eventually forming complete neural circuits [ 76 , 221 , 222 ]. Nanomaterials also have their own unique functional properties, and studies have shown that the structure and morphology of nanofibers have an impact on the therapeutic effect [ 185 , 186 , 188 ]. Fibers with a diameter of 400 nanometers were more effective in promoting cell migration and growth of protrusions than nanofibers with diameters of 800 nanometers and 1200 nanometers [ 223 ].…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…[13][14][15] Furthermore, we have recently showed how fibrous scaffolds composed of CNT induced axonal growth in injured spinal cord, thus promoting neurogenesis. 16 For this reason, CNTs have been used as growth substrates, scaffolds for nerve tissue engineering, electrode coating, and long-term implants, as well as drug delivery carriers and molecular sensors. 17,18 In our previous works, we tried to answer why CNTs have such an excellent effect on neuronal cultures.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, carbon nanotubes (CNTs) are one of the most promising materials to interface with the central nervous system (CNS), and they have shown excellent interaction with neuronal cells and ability to efficiently modulate the neuronal behavior at either the structural or functional level: CNTs boost the neuronal function, improve spontaneous synapses, and promote growth and extension of their axonal processes. Furthermore, we have recently shown how fibrous scaffolds composed of CNTs induced axonal growth in injured spinal cord, thus promoting neurogenesis . For this reason, CNTs have been used as growth substrates, scaffolds for nerve tissue engineering, electrode coating, and long-term implants, and drug delivery carriers and molecular sensors. , In our previous works, we tried to answer why CNTs have such an excellent effect on neuronal cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to rewire the injured spinal cord (SC), researchers have suggested a variety of approaches including transplantation of different cell types or biomaterials into the injury site in the acute phase. [ 5–8 ] The implantation of Schwann cells, [ 9 ] neural stem cells (NSCs) or neural progenitor cells (NPCs), [ 10,11 ] or mesenchymal stem cells [ 12 ] has been investigated as a potential therapy for SC injury. However, two issues may jeopardize the success of the treatment, namely the immune response to allogenic or xenogeneic cells, which may promote cell rejection, and implantation of dissociated cells, not organized into a functional network.…”
Section: Introductionmentioning
confidence: 99%